Brief Report: A Prospective Open‐Label Phase IIa Trial of Tocilizumab in the Treatment of Polymyalgia Rheumatica. Issue 10 (28th September 2016) - Lally, Lindsay; Forbess, Lindsy; Hatzis, Christopher; Spiera, Robert
Abstract : Objective: Interleukin‐6 (IL‐6) is a pivotal cytokine in the pathogenesis of polymyalgia rheumatica (PMR), yet the efficacy of IL‐6 blockade with tocilizumab (TCZ) for the treatment of PMR is unknown. The aim of this study was to assess the efficacy and safety of TCZ in newly diagnosed PMR. M ethods . In a single‐center open‐label study, patients with newly diagnosed PMR who had been treated with glucocorticoids (GCs) for <1 month were treated monthly with intravenous (IV) TCZ 8 mg/kg for 1 year, with a rapid tapering of GCs according to standardized protocol. The primary end point was the proportion of patients in relapse‐free remission without GC treatment at 6 months. Secondary outcome measures included duration of GC use and cumulative GC dose. Patients were followed up for 15 months. Results: Ten patients were enrolled in the study. One patient withdrew after 2 months, leaving 9 patients in whom the primary end point was assessed. The primary end point of relapse‐free remission without GC treatment at 6 months was achieved by all 9 of these patients. All patients who received TCZ treatment were able to discontinue GCs within 4 months of study entry. The cumulative mean ± SD prednisone dose was 1, 085 ± 301 mg and the total duration of GC exposure was 3.9 ± 0.9 months. Remission persisted without relapse, in all 9 patients, throughout the entire 15‐month study. Conclusion: Our findings suggest that TCZ may be an effective, safe, and well‐tolerated treatment for newly diagnosed patients with PMR, with a robust steroid‐sparing effect.